2017
DOI: 10.1101/237776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comprehensive assessment of inbreeding and laboratory adaptation inAedes aegyptimosquitoes

Abstract: Modified Aedes aegypti mosquitoes reared in laboratories are being released around the world to control wild mosquito populations and the diseases they transmit. Several efforts have failed due to poor competitiveness of the released mosquitoes. We hypothesized that colonized mosquito populations could suffer from inbreeding depression and adapt to laboratory conditions, reducing their performance in the field. We established replicate populations of Ae. aegypti mosquitoes collected from Queensland, Australia,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 99 publications
0
35
0
Order By: Relevance
“…Compared to studies performed over ten years ago, some deleterious effects of wMelPop appear weaker, particularly blood feeding traits (Moreira et al 2009b;Turley et al 2009) and male longevity (McMeniman et al 2009;Yeap et al 2011). Although this may indicate nuclear background evolution, direct comparisons with previous studies are difficult due to methodological differences and potential confounding effects of inbreeding, drift and laboratory adaptation that can occur during colony maintenance (Ross et al 2019a).…”
Section: Discussionmentioning
confidence: 94%
“…Compared to studies performed over ten years ago, some deleterious effects of wMelPop appear weaker, particularly blood feeding traits (Moreira et al 2009b;Turley et al 2009) and male longevity (McMeniman et al 2009;Yeap et al 2011). Although this may indicate nuclear background evolution, direct comparisons with previous studies are difficult due to methodological differences and potential confounding effects of inbreeding, drift and laboratory adaptation that can occur during colony maintenance (Ross et al 2019a).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, our laboratory maintenance protocol 46 should not lead to compromised host-seeking ability in the field, though other factors that can coincide with laboratory maintenance such as inbreeding may reduce fitness. 71 Different rearing procedures, such as the use of membrane feeders, non-human blood or small cages may also affect host-seeking ability if adaptation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory adaptation was studied in Ae. aegypti for 13 generations using a population size of 100 adults [43]; that study showed that small Ae. aegypti populations can suffer a fitness cost.…”
Section: Generation Influence On Cold Tolerancementioning
confidence: 97%